OTONOMI DESA DAN KESEJAHTERAAN MASYARAKAT NEGERI BATU MERAH PASCA UNDANG-UNDANG NOMOR 6 TAHUN 2014 TENTANG DESA (PERSPEKTIF HUKUM PROGRESIF) - Ahmad Lonthor (TAHKIM, 2018)
Progressive jurisdictional view to silvan autonomy and well-being country society petrifies statute position deep red number 6 years 2014 about villages if dikorelasikan therefore tend advance law aspiration for human, therefore relevansi country society energy Batu Merah who want independence in mengurusi their own village autonomy as it were have already at amanahkan by law thus principally utilize progressive law approaching is in line with culture goal sentence indonenesia who emphasizes to assess – the living one point in society.